Effectiveness Of Phacoemulsification In Post-Traumatic Cataracts - Makhmudov Narzikul Xodjanazarovich (Next Scientists International Journal JSSHRF, 2026)
Post-traumatic cataract is a common and significant cause of visual impairment following ocular injury. Advances in cataract surgery, particularly phacoemulsification, have transformed the management of traumatic cataracts by offering improved visual outcomes and faster recovery. However, post-traumatic cataracts present unique surgical challenges due to associated ocular damage such as zonular weakness, posterior capsule rupture, corneal scarring, and inflammation. This article reviews the effectiveness of phacoemulsification in the treatment of post-traumatic cataracts, focusing on surgical techniques, outcomes, complications, and prognostic factors. A comprehensive analysis of current literature suggests that phacoemulsification is a safe and effective method when appropriately selected and modified according to trauma-related pathology.